Exploring the influence of closed-circuit television in preventing bullying behaviour at a selected School in KwaZulu-Natal: A Case Study - Govender, Sumeshni (International journal of studies in psychology, 2025)
South African schools have been experiencing an increase in bullying behaviour (BB) incidents. One school in Northern KwaZulu-Natal installed closed-circuit televisions throughout the entire school as a preventive measure. Previous studies have proved that both learner-learner and teacher-targeted bullying is a serious challenge and needs immediate intervention in schools locally and globally. This study explored how the influence of closed-circuit televisions can prevent bullying behaviour in a school in the King Cetshwayo district in KwaZulu-Natal. It applied a qualitative, descriptive research design, interpretive research paradigm, and exploratory approach. Nine participants were purposively sampled, including one principal, two deputy principals, one head of department, four teachers, and one school governing body member. Thematic findings revealed that the influence of closed-circuit televisions could prevent learner and teacher-targeted bullying behaviour and improve the effectiveness of preventative behaviour in the classroom, playground, and corridors. However, teacher participants suggested including stakeholders (parents, social workers, and SAPS) involvement in mainstream school visits. In South Africa, with the Protection of Personal Information Act (Republic of South Africa, 2013), the need for permission before data collection becomes a more fundamental issue.